2019
DOI: 10.1111/puar.13139
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Motivations of Mega‐Gift Donors to Higher Education: A Qualitative Study

Abstract: Patterns of giving to higher education by individual donors have changed in recent years, with large gifts accounting for an increasing percentage of the total. In light of this shift, understanding the motivations of donors who make very large gifts, commonly known as “mega‐gifts,” has become important. Efforts to explore these motivations run into access barriers. This article uses an innovative methodological approach to overcome this challenge. Drawing on the media coverage of mega‐gifts, the authors creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 33 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…The most prestigious universities obtain more funds due to their visibility not only through donations from alumni but also from wealthy donors wishing to acquire further legitimacy, visibility, and prestige (Bekkers & Wiepking, 2011). These are research-based universities that can produce breakthrough research carrying the name of the donor associated with the research, leaving a long-lasting legacy (Worth et al, 2020). Less prestigious, teaching-oriented universities are not as appealing for potential outside donors, have less organizational experience and resources to arrange crowdfunding and other fundraising activities, and have a student population that tends to be less affluent, more diverse, and often made up of mature students with relatively low-paying jobs (Gearhart et al, 2019).…”
Section: Crowdfunding and Its Current Use In Higher Education Settingsmentioning
confidence: 99%
“…The most prestigious universities obtain more funds due to their visibility not only through donations from alumni but also from wealthy donors wishing to acquire further legitimacy, visibility, and prestige (Bekkers & Wiepking, 2011). These are research-based universities that can produce breakthrough research carrying the name of the donor associated with the research, leaving a long-lasting legacy (Worth et al, 2020). Less prestigious, teaching-oriented universities are not as appealing for potential outside donors, have less organizational experience and resources to arrange crowdfunding and other fundraising activities, and have a student population that tends to be less affluent, more diverse, and often made up of mature students with relatively low-paying jobs (Gearhart et al, 2019).…”
Section: Crowdfunding and Its Current Use In Higher Education Settingsmentioning
confidence: 99%
“…Since the letters are publicly available and written as part of joining the pledge, they may not reveal the true motivations driving philanthropic activities, but they do reveal how the pledgers would like others and the public to perceive of their generosity. Prior research on the Giving Pledge letters has identified already some of these explanations (Sadeh et al 2017 ), while earlier studies on the philanthropy of the wealthy has also generated insights into how these donors make sense of their giving (Breeze & Lloyd 2013 ; Horvath & Powell 2020 ; Schervish 2007 ; Worth et al 2019 ). A study focused on pledgers from the tech sector found that “they were more likely than the other Pledgers to have an expansive and positive vision of philanthropic endeavor” (Brockmann et al 2021 , 21).…”
Section: Explanations For Givingmentioning
confidence: 99%
“…In this endeavor, we build on two distinct bodies of literature. One is focused on elite donor culture, broadly defined, and seeks to uncover psychological motivations for giving among the wealthy (e.g., Breeze & Lloyd, 2013;Ostrower, 1995;Schervish, 2007;Worth et al 2019). The second set of studies focuses specifically on the Giving Pledge population (e.g., Coupe & Monteiro, 2016;Sadeh et al 2017) with a similar focus on extracting information about underlying motives.…”
Section: Introductionmentioning
confidence: 99%
“…Building on earlier studies of wealthy donors, we identify a dominant social-normative rationale alongside a less prevalent personal-consequentialist rationale. Rejecting a simplistic dualism of altruistic and egoistic motives for giving (Herzog & Price, 2016;Worth et al 2019), our analysis organizes a number of distinct explanations for giving into two coherent profiles (Table 6). In contrast to earlier studies of the Giving Pledge population, we consider the letters not just as vessels of data to derive individual motives, but as social products of, and contributions to elite philanthropic discourse.…”
Section: Introductionmentioning
confidence: 99%